Site-specific Approach to Reducing Emergency Department Visits Following Surgery. Issue 4 (April 2018) - Abdel Khalik, Hassaan; Stevens, Haley; Carlin, Arthur M.; Stricklen, Amanda; Ross, Rachel; Pesta, Carl; Finks, Jonathan F.; Ibrahim, Andrew; Ghaferi, Amir A.
Abstract : Objective: The aim of this study was to explore the efficacy of current bariatric perioperative measures at reducing emergency department (ED) visits following bariatric surgery in the state of Michigan. Summary of Background Data: Many ED visits following bariatric surgery do not result in readmission and may be preventable. Little research exists evaluating the efficacy of perioperative measures aimed at reducing ED visits in this population. Therefore, understanding the driving factors behind these preventable ED visits may be a fruitful approach to prevention. Furthermore, evaluating the efficacy of current perioperative measures may shed light on how to achieve meaningful reductions in ED visits. Methods: We studied 48, 035 eligible bariatric surgery patients across 37 Michigan Bariatric Surgical Collaborative (MBSC) sites between January 2012 and October 2015. Hospitals were ranked according to their risk- and reliability-adjusted ED visit rates. For hospitals in each ED visit rate tercile, several patient, surgery, and hospital summary characteristics were compared. We then studied whether a hospital's compliance with specific perioperative measures was significantly associated with reduced ED visit rates. Results: Only 3 of the 30 surgery, hospital, and patient summary characteristics studied were significant predictors of a hospital's ED visit rate: rate of sleeve gastrectomies, rate of readmissions, and rate of venous thromboembolism complications ( P = 0.04, P = 0.0065, and P = 0.0047, respectively). Also, a hospital's compliance with the perioperative measures evaluated was not a significant predictor of ED visit rates ( P = 0.12). Conclusions: Current practices aimed at reducing ED visits appear to be ineffective. Due to heterogeneity in patient populations and local infrastructure, a more tailored approach to ED visit reduction may be more successful.